Ethnic Identity and Second Language Learning. (13th March 2015) - Trofimovich, Pavel; TuruÅ¡eva, Larisa
ABSTRACT Ethnic identity refers to the subjective experience embracing the feelings, experiences, and behaviors through which people position their membership in a single or multiple ethnic groups. The goal of this article is to integrate evidence from social psychology and applied linguistics, by focusing on the identityâ€"language link from the perspective most relevant to second language (L2) development, namely, by considering how ethnic identity might be implicated in L2 learning. We first define and contextualize ethnic identity and its possible relationships to language. We then review recent empirical evidence for the link between ethnic identity and L2 measures, and we speculate on whether this link represents a bidirectional relationship whereby ethnic identity and language are interlocked through self-reinforcing processes and mediated through language usersâ€™ experience with language. We conclude by framing research on ethnic identity within sociocognitive views of L2 learning and describe several possible avenues for advancing this area of research.